Scanning Electron Microscope Studies on Ornamentation of Egg Chorion of Capissa vagesa (Moore, 1859) (Erebidae) and Trabala vishnou (Lefèbvre, 1827) (Lasiocampidae) (Ditrysia: Lepidoptera) from India (Journal of the Entomological Research Society, 2023)
The eggs of Capissa vagesa (Moore, 1859) and Trabala vishnou (Lefèbvre, 1827) from the families Erebidae and Lasiocampidae were examined and characterized under scanning electron microscope. Significant morphological traits on the eggshells of both analyzed species are presented in current study. Descriptions and comparative morphological assessments for both species of these moths are provided, in addition to the structural complexity of the eggs uncovered throughout the course of this study. This study showed that ultrastructural egg chorion features investigated in the current study i.e., shape of Micropylar rosette, polygonal cells, number of micropyles and aeropyles have high taxonomic significance at specific and generic levels, and these sort of investigations must be expanded to improve and elevate the morphological depiction at levels of earlier life stages in various moth families.